(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
The article discusses the issues of pedagogical study of competitive activities of highly qualified football players. In the research process, methods of analysis of scientific literature, pedagogical observation, recording of technical and tactical actions and statistical processing were used. The Wyscout platform was used to determine and analyze the performance of football players. This approach demonstrates the importance of complex pedagogical control in assessing the preparation and increasing the effectiveness of football players